Improving language teaching and learning through neurolinguistic programming - Arthur, Christine Shobana * (2012)
Research has shown that proficient language learners who are also called ‘Self-Directed Learners’ and ‘Good Language Learners’ constantly have successful language learning experiences. They are known to be motivated, independent, flexible and creative language learners compared to the less proficient learners. This leads us to the question, “Why do proficient English as Second Language (ESL)learners have more successful language learning experiences as compared to the less proficient ESL learners? Are the less proficient learners deemed to have bad language learning experience all the time?” This paper suggests various Neurolinguistic Programming (NLP) models that can be used by the less proficient learners who can also reach autonomy in acquiring their second language. Therefore, this paper aims to connect language teaching with learners’ cognitive behaviour in order to improve, particularly, the less proficient language learners’ learning experience through NLP. The outcome of the present study would be useful to assist language instructors in helping the less proficient ESL learners to undergo a more effective and successful second language learning experience.